Identification of priority areas for landscape connectivity maintenance in the Xingu Area of Endemism in Brazilian Amazonia - CASTRO,Rodrigo Baia (2020)
ABSTRACT Forest fragmentation has been intense in the eastern Amazon region, which has negatively affected wildlife populations. The speed of deforestation in this region underscores the urgent need to understand the effects of such changes on populations of endemic species, and to implement measures for ecosystem conservation. We analyzed the extent to which fragmented forests are still connected in the Xingu Area of Endemism, in the eastern Brazilian Amazon, and assigned conservation priority to fragments most important for connectivity maintenance. We structurally classified the Xingu landscape using the Morphological Spatial Pattern Analysis and ranked each fragment according to its importance using an Index of Connectivity. Our data revealed important differences in conservation potential across the region. Although most of the study area already receives some degree of protection, future conservation actions should prioritize the connection of habitat fragments to maximize dispersal potential and minimize genetic isolation of biodiversity components. We produced a map of prioritary areas for connectivity maximization. These areas include fragments with large core areas and high-quality fragments that provide connection among habitats which, together, should maintain crucial corridors for gene flow in a biologically-rich region of the Amazon.